And up she went – The moral vertical in Wings - Høgetveit, Åsne Ø. (Nordlit, 2017)
This article is dedicated to the film Wings (1966) directed by the Soviet director Larisa Shepitko. With its story of a World War II veteran, Nadezhda Stepanovna Petrukhina, Wings makes for an interesting case when looking at women’s and veteran’s status in the Soviet society of the 1960’s, and morality and memory culture more generally speaking. But as Nadezhda Stepanovna is a former fighter pilot who continuously return to the sky in her daydreams, Wings is also an excellent case for a critical discussion of the meaning of the airspace. Aviation and the airspace hold certain connotations is Russian culture (not necessarily excluding other cultures) that open up for a different kind of reading of this film, in particular because of the intersections between gender, space and memory. Hierarchies are often presented trough a metaphor of verticality in Russian culture. By examining the different notions of verticality, both physical and metaphorical, in Wings, I not only argue that this film can be read in a new way, but also bring new perspectives on the established theory of women’s position in Russian culture as morally superior to men. This again can be linked back to the spatial understanding of Russia, as the term Motherland in Russia particularly strongly makes a connection between femininity, the mother, and space, the land.